2020
DOI: 10.1093/mnras/staa3207
|View full text |Cite
|
Sign up to set email alerts
|

IllustrisTNG and S2COSMOS: possible conflicts in the evolution of neutral gas and dust

Abstract: We investigate the evolution in galactic dust mass over cosmic time through i) empirically derived dust masses using stacked submillimetre fluxes at 850μm in the COSMOS field, and ii) dust masses derived using a robust post-processing method on the results from the cosmological hydrodynamical simulation IllustrisTNG. We effectively perform a ‘self-calibration’ of the dust mass absorption coefficient by forcing the model and observations to agree at low redshift and then compare the evolution shown by the obser… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 149 publications
(263 reference statements)
0
6
0
Order By: Relevance
“…Other simulations found that they require a variable DTM in order to reproduce the UV luminosity of low-mass high-redshift galaxies (Lagos et al 2019;Vogelsberger et al 2020). This assumption is different from the classical one of a constant DTM of ∼ 0.3 often adopted in simulation-based works (see for example Cochrane et al 2019;Schulz et al 2020;Liang et al 2020;Millard et al 2021).…”
Section: Implications For (Future) Observationsmentioning
confidence: 89%
“…Other simulations found that they require a variable DTM in order to reproduce the UV luminosity of low-mass high-redshift galaxies (Lagos et al 2019;Vogelsberger et al 2020). This assumption is different from the classical one of a constant DTM of ∼ 0.3 often adopted in simulation-based works (see for example Cochrane et al 2019;Schulz et al 2020;Liang et al 2020;Millard et al 2021).…”
Section: Implications For (Future) Observationsmentioning
confidence: 89%
“…Other simulations found that they require a variable DTM in order to reproduce the UV luminosity of low-mass high-redshift galaxies (Lagos et al 2019 ;Vogelsberger et al 2020 ). This assumption is different from the classical one of a constant DTM of ∼0.3 often adopted in simulation-based works (see for example Cochrane et al 2019 ;Liang et al 2020 ;Schulz et al 2020 ;Millard et al 2021 ).…”
Section: Ac K N Ow L E D G E M E N T Smentioning
confidence: 89%
“…Finally, we compliment our analysis by comparing our DMF to the theoretical predictions of the HAGN and Il-lustrisTNG simulations (Millard et al 2020). In order to produce a HAGN DMF, we define a simulated sample following the procedure described above, bin the galaxies in 0.4 dex intervals of M dust , and normalise by the volume of the simulation (4 × (142) 3 Mpc 3 ).…”
Section: On the Dmfs And The Theoretical Predictionsmentioning
confidence: 99%
“…In order to produce a HAGN DMF, we define a simulated sample following the procedure described above, bin the galaxies in 0.4 dex intervals of M dust , and normalise by the volume of the simulation (4 × (142) 3 Mpc 3 ). For the IllustrisTNG simulation, Millard et al (2020) consider multiple TNG100 snapshots in a box size of 106 Mpc per side, comparable to the HAGN simulated subset presented earlier. The TNG-DMF is constructed through the M dust values of the simulated galaxies, derived in post-processing through a fixed dust-to-metals ratio of 0.5.…”
Section: On the Dmfs And The Theoretical Predictionsmentioning
confidence: 99%